New names for junior homonyms in Scydmaeninae (Coleoptera, Staphylinidae) - Jałoszyński, Paweł; Newton, Alfred F. (Zootaxa, 2020)
As in most species-rich groups, cases of homonymy are not uncommon among Scydmaeninae. Many primary and secondary junior homonyms were recently replaced by O’Keefe (2000), Davies (2004), Davies & Vít (2004), Castellini (2010), Jałoszyński (2011), Asenjo (2016), and Newton (2017). One new primary homonym has been published since then, and changes in generic placement (Jałoszyński 2013, 2020a) have generated several new secondary homonyms. New names for those are proposed below.